2017
DOI: 10.1007/s11284-017-1475-y
|View full text |Cite
|
Sign up to set email alerts
|

Local neighborhood communities in the understory play a critical role by affecting regeneration niches and subsequent community assembly in a montane cloud forest

Abstract: Regeneration niches for tree seedlings are defined as possessing the biotic and abiotic requirements to successfully replace adults. However, two critical discrepancies obscure our understanding of the role of regeneration niches in forest community assembly: a weak association between seedling assemblages and environmental factors, and an uncoupling between seedling and adult‐tree assemblages. However, understory plants, which may interact with microenvironments and seedlings, may be a better spatial descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Overstorey shading and litter size, quality and quantity are significant filters for vascular seedling establishment (Gillman & Ogden, 2001;Ibáñez, Clark, LaDeau, & Lambers, 2007;Valladares, Laanisto, Niinemets, & Zavala, 2016). These biotic drivers are commonly considered under the dominant influence of canopy species, but understorey vegetation can also contribute to the forest regeneration niche (Caccia, Chaneton, & Kitzberger, 2009;Farris-Lopez, Denslow, Moser, & Passmore, 2004;Takahashi, 1997;Weng, Yang, Hsieh, Hsieh, & Su, 2017). Demonstrating biotic influence on community assembly requires careful consideration of a suite of processes including dispersal limitations, environmental filters and within-site heterogeneity (Kraft et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Overstorey shading and litter size, quality and quantity are significant filters for vascular seedling establishment (Gillman & Ogden, 2001;Ibáñez, Clark, LaDeau, & Lambers, 2007;Valladares, Laanisto, Niinemets, & Zavala, 2016). These biotic drivers are commonly considered under the dominant influence of canopy species, but understorey vegetation can also contribute to the forest regeneration niche (Caccia, Chaneton, & Kitzberger, 2009;Farris-Lopez, Denslow, Moser, & Passmore, 2004;Takahashi, 1997;Weng, Yang, Hsieh, Hsieh, & Su, 2017). Demonstrating biotic influence on community assembly requires careful consideration of a suite of processes including dispersal limitations, environmental filters and within-site heterogeneity (Kraft et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These theories are roughly categorized into deterministic and stochastic views. The deterministic view focuses on environments as direct determinants of community structure, because these can directly affect physiological processes of species or, indirectly, biological interactions such as competition and predation (e.g., Weng et al 2017). Some community ecology theories, e.g., ''Paradox of plankton'' (Hutchinson 1961), theories of keystone species (Paine 1969), and trophic cascade (Carpenter and Kitchell 1996), rely on such deterministic forces.…”
Section: Strengthen Links Between Ecological and Social Systemsmentioning
confidence: 99%
“…Laplace et al (2017) showed greater stand transpiration in Moso bamboo forests than that in a surrounding Japanese cedar plantation in both Taiwan and Japan, although their seasonality was very different across the two countries. Weng et al (2017) examined a weak association between seedling distribution and environmental factors in a montane cloud forest of Taiwan. They showed a stronger link to habitat association of seedling assemblages using the spatial structure of understory plants.…”
Section: Filling Gaps In Ecological Studiesmentioning
confidence: 99%